Mental health problems across three generations of Australian families - Hancock, K; Hancock, K.J.; Lawrence, D; Zubrick, S.R.; Zubrick, S; Mitrou, F; Shipley, M (My University, 2013)
Research has consistently shown that children of parents with mental illness are at greater risk of developing mental illness, however few studies have examined the impact of familial mental health problems beyond the parent-child relationship. Using mental health data collected from 4600 families in Growing Up in Australia: The Longitudinal Study of Australian Children, this study examined mental health relationships across three generations of families. Children scoring >=14 on the Strengths and Difficulties Questionnaire were classified as experiencing social-emotional wellbeing (SEWB) problems. Compared to children with no family history of mental health problems, children who had a grandparent, but not a parent, with a history of mental health problems were 1.32 times (95% CI 1.07-1.64) more likely to have SEWB problems. They were 3.20 (95% CI 2.26-4.52) times as likely to have SEWB problems if they had a parent, but no grandparent, with a mental health problem and 2.58 (95% CI 1.91-3.49) times as likely to have SEWB problems if they had both a parent and a grandparent with a mental health problem. The results indicate that the mental health histories of both parents and grandparents are an important influence on the social-emotional wellbeing of young children.
Keywords: Child Development -- Emotional; Intergenerational Transfer; Health -- Mental; Families; Families and relationships; Health and wellbeing; Childhood and child development; Intergenerational Transfer; Health; Families; Child Development; Emotional; Mental; Families and relationships; Childhood and child development; Health and wellbeing